الاحتياجات التعليمية لدى مرضى الداء السكري النوع الثاني في مستشفى تشرين الجامعي بمدينة اللاذقية. - نظاملي فريال (Latakia University Journal -Medical Sciences Series, 2018)
- المقدمة: يعد مرض السكري وباء عالمي وسبب لزيادة الوفيات و الامراضية. وعلى الرغم من وجود سياسات الوقاية والرعاية، فإنه لا يزال يشكل مشكلة صحية عالمية ذات مضاعفات خطيرة وكبيرة. - الهدف: يهدف هذا البحث إلى تقييم الاحتياجات التعليمية لدى مرضى الداء السكري والتعرف على مستوى المعرفة لديهم، والصفات الديموغرافية التي ترتبط بهذه المعرفة. - مواد وطرق البحث: أجريت هذه الدراسة الوصفية المقطعية في مستشفى تشرين الجامعي باللاذقية على عينة مؤلفة من50 مريضا مراجعا في الفترة الواقعة بين أيار 2017 وكانون الأول 2017. تم جمع البيانات باستخدام استبيان لتقييم المعرفة حول الداء السكري، المضاعفات، العلاج الدوائي، نمط الحياة، الأعراض والوقاية. تم اعتبار 70% وما فوق مستوى جيد للمعرفة و30- 70 % مستوى متوسط، 30% ومادون مستوى ضعيف للمعرفة. - النتائج: بينت الدراسة أن أكثر ن نصف العينة 54% كانت < 50 عاما وأن نسبة 54% ذكور و 46% إناثا، كما بينت أن أهم الاحتياجات التعليمية كانت متعلقة بالأنسولين وأنواعه وتأثيراته الجانبية، كيفية تفادي حدوث القدم السكرية والعناية بها. كما أظهرت الدراسة أن مستوى المعرفة لدى العينة كان متوسطا 63%. - التوصيات: المعرفة المتعلقة بالداء السكري في جميع جوانبه تحتاج لأن تكون أفضل وذلك للسيطرة على المرض ومضاعفاته. يوصى بإجراء دراسات مستقبلية حول تأثير تطبيق برنامج تثقيفي في تحسين مستوى المعرفة والعناية الذاتية للمرضى فيما يتعلق بالقدم السكرية. introduction: Diabetes mellitus is a global epidemic and a leading cause for increasing mortality and morbidity. Although prevention and care policies exist, diabetes continues to be a global public health problem with serious consequences. Aim: To assess the educational needs on diabetes among patients, level of knowledge and patient specific characteristics that are associated with this knowledge. Method: A descriptive study was conducted among 50 patients who entered Tishreen university between May 2017 and December 2017. Questionnaire on different domains of diabetes such as general knowledge, complications, treatment, life style, symptoms and prevention. Each statement was given a score of one if it was answered correctly and zero for a wrong answer. Out of a total score, a score of seventy percent and above was considered good knowledge , between thirty percent and seventy considered moderate, less than thirty considered poor knowledge . Results: more than half, were > 50 years (54%), (54%) were males, 46% were female. Most of educational needs were: regarding of insulin, its kinds, sides effects, methods of prevention of diabetic foot and care it. The level of knowledge of diabetes was moderate 63%. Recommendation: Awareness regarding all the aspects of diabetes mellitus needs to be increased for better control of the disease and its complications. Future studies about effect of education program on improvement of knowledge and self care, especially about the diabetic foot.